INTEGRASI NILAI SEJARAH LOKAL DALAM BAHAN AJAR BAHASA INDONESIA UNTUK MENINGKATKAN LITERASI DAN KESADARAN SEJARAH SISWA - Zatmiko Ayatulloh, Ahmad; Sulthoni, Ahmad (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to analyze how the integration of local historical values ??in Indonesian language teaching materials can improve students' literacy and historical awareness. The focus of the study included high school students with a scope of narrative, expository, and argumentative teaching texts adapted from local historical events or figures. The approach used was descriptive qualitative with critical literacy theory (Freire) and historical awareness as conceptual foundations. Data collection was carried out through teacher interviews, documentation studies of teaching materials, and content analysis of teaching materials. The data model studied was in the form of local historical narratives such as folklore, the struggles of local figures, and local historical events used in reading and writing activities in Indonesian language classes. The results of the study showed that the use of local history-based teaching materials was able to increase student engagement, strengthen reading comprehension, and motivate students in writing and discussing. Interesting findings showed that students felt more emotionally connected to the material, and began to develop a sense of historical identity and empathy. This integration has proven to not only strengthen literacy, but also be an effective strategy in instilling local historical and cultural values ??in cross-disciplinary learning.